The effect of tongue appliance on the nasomaxillary complex in growing cleft lip and palate patients - Jamilian A; Showkatbakhsh R; Boushehry M (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2006)
Midfacial deficiency is a common feature of cleft lip and palate patients due to scar tissue of the lip and palate closure procedure. The aim of this study was to evaluate the effectiveness of the physiological force of the tongue to move the maxilla in forward position. This research has been done experimentally by, before and after treatment following up in private practice. Ten patients (6 female, 4 male) with complete bilateral cleft lip and palate were selected. All of them had Cl III malocclusion with maxillary deficiency due to scar tissue of lip and palate surgery. Their age ranged from 7.6 to 9.8 years. All the patients were delivered tongue appliance to transfer the force of the tongue to maxillary complex. The mean observation time was 13±2 months to achieve positive overjet. Pre- and post-lateral cephalograms were compared to evaluate the skeletal changes with paired t-test. The results showed that after the application of tongue appliance, normal sagittal maxillomandibular relationship was achieved. SN-ANS angle was increased 1.9±1.8 - P < 0.05. Nasolabial angle was decreased 10.3±10.8 - P < 0.03. This study showed that the tongue appliance could transfer considerable force during rest and swallowing period to the maxilla. This method might be considered to improve the deficient maxilla by means of growth modification and redirect concept.